Chapter 8 The music editions of Christian Egenolff a new catalogue and its implications - Gustavson, Royston (Taylor & Francis, 2018)
The present chapter, based on a first-hand examination of all of Egenolff's music editions, including every known exemplar of ten of the fourteen extant editions, aims to remedy this, so that future work on Egenolff and the music in his editions can rest on a surer bibliographical foundation. The catalogue closes with a number of titles that either do not in fact contain printed music, or the printing of which is hypothesised